Propostas para avaliação de desempenho dos empregados de uma sociedade de economia mista : um estudo de caso em uma empresa de grande porte - Costa, Leonardo Carneiro da (2016)
This research is a product of a case study of an improvement process on employees’ performance assessment and management that happened in a large mixed economy company. This is a descriptive research beyond an exploratory and qualitative approach, using case study to confront practice with theory. Therefore, this research consists in, firstly, identifying the problems faced for the company during the improvement process, the changes happened at the employees’ performance assessment and management and the company’s objectives with these changes implementation. Posteriorly, problems that persists at the employees’ performance assessment and management after the improvement process were identified and, grounded in scientific productions about these theme, proposes of solutions to these problems were done.